The Effects of Waste‐Based and Thermal Energy‐Storing Building Materials on Sustainable Architecture: A Review - Kılıç Bakırhan, Ebru; Tuna Kayılı, Merve (Engineering reports (Hoboken, N.J.), 2025)
ABSTRACT The utilization of waste‐based thermal energy‐storing building materials in construction is a significant advancement in the reduction of the environmental impact of human activities. Such materials provide thermal comfort, reduce energy consumption, and promote the use of renewable resources. Phase change materials (PCM) have been the subject of these achievements in recent years regarding their heat storage potentials. On the other hand, the utilization of waste is of significant consequence with regard to the sustenance of a circular economy and the alleviation of waste‐related environmental concerns. However, the majority of studies on PCM in the literature tend to concentrate on the thermal, physical, chemical, and mechanical properties of the materials, and thus fails to provide a comprehensive perspective on the sustainability of these materials. In this study, 11 articles selected from a total of 178 studies aiming to produce building materials with waste‐PCM combinations are analyzed according to five categories related to sustainable built environment, which are resource use, environmental impact, health, comfort, and cost. As a result, it is proved that composite building materials that contain waste and store thermal energy have the potential to contribute significantly to sustainable architecture. The utilization of waste‐based, thermal energy‐storing building materials in construction may help reduce the environmental impact of human activities. However, most studies on phase change materials (PCM) tend to concentrate on the basic properties of these materials, and thus fail to provide a comprehensive perspective on sustainability. This review aims to present both the advantages and blind spots of waste utilization.